Marginal land suitability for switchgrass, Miscanthus and hybrid poplar in the Upper Mississippi River Basin (UMRB). (July 2017) - Feng, Qingyu; Chaubey, Indrajeet; Engel, Bernard; Cibin, Raj; Sudheer, K.P.; Volenec, Jeffrey
Abstract: Marginal lands are recommended as a viable land resource for biofeedstocks production, but their suitability for biofeedstock crops growth are poorly understood. This study assessed the suitability of marginal lands in Upper Mississippi River Basin (UMRB) for three promising biofeedstock crops, switchgrass, Miscanthus and hybrid poplar. The land suitability was categorized into 5 suitability classes (not-, poorly-, moderately-, good- and highly-suitable) based on a fuzzy logic based land suitability evaluation procedure. The results showed that 60% of marginal lands in UMRB were moderately to highly suitable for growth of the targeted biofeedstock crops. Predicted bioethanol production from marginal land in the UMRB with consideration of suitability level was two thirds of the production predicted without consideration of suitability level. Our results better constrain the potential of marginal land for biofuel production as well as the importance of land suitability evaluation for policy analysis targeting biofuel development on marginal lands. Highlights: 23% of the UMRB region are marginal lands. Land suitability procedure based on fuzzy logic theory is used. 60% of marginal land are moderately to highly suitable for growth of switchgrass, Miscanthus and hybrid poplar. Biofuel production prediction with marginal land suitability is 2/3 of that without marginal land suitability. Producing bioenergy crops on marginal land in the UMRB can help reduce the food vs. fuel competition for land.